Nitrogen acquisition strategy and its effects on invasiveness of a subtropical invasive plant - Guan, Ming; Pan, Xiao-Cui; Sun, Jian-Kun; Chen, Ji-Xin; Kong, De-Liang; Feng, Yu-Long (Frontiers in Plant Science, 2023)
Preference and plasticity in nitrogen (N) form uptake are the main strategies with which plants absorb soil N. However, little effort has been made to explore effects of N form acquisition strategies, especially the plasticity, on invasiveness of exotic plants, although many studies have determined the effects of N levels (e.g. N deposition). To address this problem, we studied the differences in N form acquisition strategies between the invasive plant Solidago canadensis and its co-occurring native plant Artemisia lavandulaefolia, effects of soil N environments, and the relationship between N form acquisition strategy of S. canadensis and its invasiveness using a 15N-labeling technique in three habitats at four field sites. Total biomass, root biomass, and the uptakes of soil dissolved inorganic N (DIN) per quadrat were higher for the invasive relative to the native species in all three habitats. The invader always preferred dominant soil N forms: NH4+ in habitats with NH4+ as the dominant DIN and NO3- in habitats with NO3- as the dominant DIN, while A. lavandulaefolia consistently preferred NO3- in all habitats. Plasticity in N form uptake was higher in the invasive relative to the native species, especially in the farmland. Plant N form acquisition strategy was influenced by both DIN levels and the proportions of different N forms (NO3-/NH4+) as judged by their negative effects on the proportional contributions of NH4+ to plant N (fNH4+) and the preference for NH4+ (βNH4+). In addition, total biomass was positively associated with fNH4+ or βNH4+ for S. canadensis, while negatively for A. lavandulaefolia. Interestingly, the species may prefer to absorb NH4+ when soil DIN and/or NO3-/NH4+ ratio were low, and root to shoot ratio may be affected by plant nutrient status per se, rather than by soil nutrient availability. Our results indicate that the superior N form acquisition strategy of the invader contributes to its higher N uptake, and therefore to its invasiveness in different habitats, improving our understanding of invasiveness of exotic plants in diverse habitats in terms of utilization of different N forms.